2021
DOI: 10.1093/plphys/kiab586
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of bud outgrowth varies at cauline and rosette nodes in Arabidopsis thaliana

Abstract: Shoot branching is a complex mechanism in which secondary shoots grow from buds that are initiated from meristems established in leaf axils. The model plant Arabidopsis (Arabidopsis thaliana) has a rosette leaf growth pattern in the vegetative stage. After flowering initiation, the main stem elongates with the top leaf primordia developing into cauline leaves. Meristems in Arabidopsis initiate in the axils of rosette or cauline leaves, giving rise to rosette or cauline buds, respectively. Plasticity in the pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…These results confirmed the possibility that the bushy appearance of SJP1/2 was partially caused by repressing ZjBRC1 -controlled ABA accumulation in the buds. It was noticed that there was a large discrepancy in leaf area between plants, which might account for differences in branch numbers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed the possibility that the bushy appearance of SJP1/2 was partially caused by repressing ZjBRC1 -controlled ABA accumulation in the buds. It was noticed that there was a large discrepancy in leaf area between plants, which might account for differences in branch numbers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…BRC1 is also a key integrator of light quality, in particular the response to plant density and to changes to the ratio of red to far-red (R:FR) wavelengths of light ( Finlayson et al , 2010 ; González-Grandío et al , 2013 ). Reduced shoot branching is part of the shade avoidance response which commonly also includes increased plant height and early flowering time ( Casal, 2012 ; Fichtner et al , 2022 ). In sorghum and Arabidopsis, it was shown that high planting density and a low R:FR ratio results in high TB1/BRC1 expression and reduced shoot branching/tillering ( Kebrom et al , 2006 ; Aguilar-Martínez et al , 2007 ; Finlayson et al , 2010 ; González-Grandío et al , 2013 ).…”
Section: Role Of Light In Shoot Branchingmentioning
confidence: 99%
“…2022 ). Since any variation in the rosette leaf number impacts the rosette branch number in highly branched arabidopsis genotypes ( Fichtner et al. 2022 ), it needs to be determined if wild-type rootstocks can reduce rosette branching in clamt mutant scions when branching is measured as rosette branches per rosette leaf as seen in lbo ( Brewer et al.…”
Section: Sl and Sl Precursor Transport For Regulation Of Branchingmentioning
confidence: 99%
“…This should be a focus of future research, including potential roles in integrating reproductive strategy, as it has been shown that the reproductive strategy, circadian clock and flowering time affect branching ( Beveridge et al. 2003 , Fichtner et al. 2022 , F. Wang et al.…”
Section: Future Perspectives and Challenges Aheadmentioning
confidence: 99%